Morphological aspects of coconut anther culture derived structures - Perera, Prasanthi I.P.; Yakandawala, D.M.D.; Verdeil, JL; Hocher, V; Weerakoon, LK (Sri Lanka Journals Online, 2010)
Anthers excised from male flowers of an adult coconut palm of Sri Lanka Tall cultivar were used to produce plants via androgenesis. Morphological aspects of the anther-derived structures and their plant regeneration pathways were studied. Under the culture conditions employed, both calli and embryo-mediated plant regeneration were observed. Two types of embryos with different germination patterns were identified-one with a germination point and the other type with a blunt haustorium without a prominent germination point which converted into germinated embryos. Three types of calli (embryogenic compact calli, embryogenic friable calli and non-embryogenic fast-growing calli) were also produced and the most commonly identified type was embryogenic compact calli that give rise to somatic embryos. Secondary somatic embryos were produced in both direct embryo and callus mediated embryogenesis. Normal plants with a single shoot were observed in low frequencies while weak plantlets with multiple shoot were observed in abundance. Under similar culture conditions, some plantlets showed vigorous growth whereas the majority had a slow growth rate.